“El dios cansado”: la muerte de dios y el triunfo de la poesía en la escritura de José María Eguren - Vargas Canchanya, Martín (2024)
This article analyzes the religious subtext of “El dios cansado”, one of the best-known poems by José María Eguren (1874-1942). The analysis focuses on the representation of the divine in this text and the multiple enunciative operations from which a critique of the image of the Christian divinity is formulated. Within the framework of a reflection on nihilism and the crisis of enlightened rationalism, it tries to demonstrate how in the analyzed poem Eguren’s writing assumes the Nietzschean topic of the death of God to reinterpret the image of the divine, reveal the inconsistency of the hegemonic discourses and reconsider the place of poetic saying in front of the sacred.